Non-Robotic Endoscopic-Assisted Internal Mammary Artery Harvest—A Historical Review and Recent Advancements - De Qing Görtzen; Fleur Sampon; Joost Ter Woorst; Ferdi Akca (Journal of Cardiovascular Development and Disease)
Background: The non-robotic endoscopic harvest of the internal mammary artery (IMA) facilitates minimally invasive bypass grafting while minimizing chest wall trauma. The technique was pioneered in the early 1990s and has recently regained popularity due to its accessibility and reproducibility. This review aims to provide an overview of endoscopic IMA harvest from its inception to the present. Methods: In August 2024, a literature search was performed using the electronic databases of the Cochrane Controlled Trials Register (CCTR) and PubMed. To obtain optimal search results, the keywords “thoracoscopic”, “endoscopic”, “minimally invasive”, “video-assisted”, “video-assisted thoracoscopic surgery VATS”, and “internal mammary artery” or “internal thoracic artery” were used, excluding the term “robotic”. References from the extracted articles were also reviewed to identify additional studies on endoscopic IMA harvest. Results: A total of 17 articles were included in the final analysis. Left internal mammary artery (LIMA) harvest times of between 17 and 164 min were reported, with an injury to LIMA rates between 0.7 and 2.2%. Conclusions: After a 15-year period without scientific publications, interest in the endoscopic-assisted approach has rekindled in recent years due to the reduction in chest trauma compared to direct vision harvest and the widespread availability of conventional endoscopic tools. This renewed focus underscores the potential to make minimally invasive coronary surgery available in all centers.